Contact Englishes of the Eastern Caribbean - Aceto, Michael; Williams, Jeffrey P. (Jeffrey Payne), 1958- (Varieties of English around the world. General series, 2003)
Contact Englishes of the Eastern Caribbean is the first collection to focus, via primary linguistic fieldwork, on the underrepresented and neglected area of the Anglophone Eastern Caribbean. The following islands are included: The Virgin Islands (USA & British), Anguilla, Barbuda, Dominica, St. Lucia, Carriacou, Barbados, Trinidad, and Guyana. In an effort to be as inclusive as possible, the contiguous areas of the Bahamas and the Turks and Caicos islands (often considered part of North American Englishes) are also included. Papers in this volume explore all aspects of language study, includin.